The effect of experienced individuals on navigation by king penguin chick pairs. (June 2015) - Nesterova, Anna P.; Flack, Andrea; van Loon, E. Emiel; Bonadonna, Francesco; Biro, Dora
Abstract : Group members' individual experience can have important influences when navigating collectively. However, how exactly they structure group travel performance is still not fully understood. This study investigated how navigation and leadership dynamics are affected by the presence of an experienced individual in king penguin, Aptenodytes patagonicus, chick pairs. We tested pairs of chicks in which two partners differed in their level of prior navigational experience. Naïve pairs consisted of two chicks that had no previous homing experience. In mixed pairs, one chick was naïve, but the other chick had previous homing experience. Our results showed that in mixed pairs the navigational performance of naïve chicks improved if they travelled together with an experienced partner compared to when they walked alone. Experienced chicks, however, maintained their relatively high speeds and efficiencies irrespective of whether they walked with a partner or independently. We also observed a shift in leadership dynamics: in naïve pairs, both chicks took turns in leading and following, while in mixed pairs, experienced chicks tended to lead throughout. Our work provides a valuable empirical system in which to test theoretical models of leadership and information transfer within groups. Highlights: Experience and navigation in king penguin chick pairs, a field study. Chicks improve their navigation with experience. Naïve chicks navigate better when they travel together with an experienced chick. Experienced chicks lead their naïve partners.